Internal and External Factors’ Influence on Recycling: Insights From a Laboratory Experiment With Observed Behavior - Linder, Noah; Rosenthal, Sonny; Sörqvist, Patrik; Barthel, Stephan (Frontiers in Psychology, 2021)
Internal psychological factors, such as intentions and personal norms, are central predictors of pro-environmental behavior in many models, whereas the influence from external factors such as the physical environment is seldom considered. Even rarer, is studying how internal factors interacts with the physical context in which decision takes place. In the current study, we addressed the relative influence and interaction of psychological and environmental factors on pro-environmental behavior. A laboratory experiment presented participants (N = 404) with a choice to dispatch a used plastic cup in a recycling- or general waste bin after participating in a staged “yogurt taste-test”. Results showed how the spatial positioning of bins explained more than half of the variance in recycling behavior whilst self-reported recycling intentions were not related to which bin they used. Rinsing cups (to reduce contamination) before recycling, was related to both behavioral intention and external factors, although participants only followed their intentions to rinse when a prompt was present. These results show that even seemingly small differences in a choice context can influences how well intrinsic motivation predicts behavior and how aspects of the physical environment can assist the alignment of behavior and intentions, as well as steering behavior regardless of motivation.